HEALTH AND QUALITY ANALYSIS OF PORK BASED ON DISTRIBUTION CHAINS - Swacita, Ida Bagus Ngurah; Suada, I Ketut; Sitepu, Agung Denlira; Tasia, Agnes - (Buletin Veteriner Udayana, 2021)
WHO states that about 75% of new diseases affecting humans in the last two decades are caused by pathogens derived from animals or animal products, so that food products of animal origin (meat) are potentially harmful to consumers. Therefore, the health and food safety aspects of animal origin (meat) need special attention. This research aimed to analyze the health and quality of pork from the abattoir/pig slaughterhouse to its circulation chain (meat stall/market). This research used a qualitative explorative method that is analyzing pig's health by inspection, palpation, and incision and the quality of pork is subjectively examined include color, aroma, consistency, and texture test, and objective test includes the test of Water Holding Capacity, Water Content, pH, and early decay. The research sample was taken from Pesanggaran and Dharmasaba abattoir and its distribution place (meat stall in Badung and Kereneng market), with 100 samples. The data of the research were analyzed qualitative descriptively. The results showed that pork from the production site to its distribution, good health. Similarly, pork from the production site (Pesanggaran abattoir and Dharmasaba) to the distribution (Badung and Kereneng market) is good. It can be concluded that pork's health and quality from production place until its distribution chains is still good, so it can be recommended healthy, safe, and feasible to be consumed.